Vaccine complacency and dose distribution inequities limit the benefits of seasonal influenza vaccination, despite a positive trend in use. Issue 41 (1st October 2021) - Palache, Abraham; Rockman, Steven; Taylor, Beverly; Akcay, Meral; Billington, John K; Barbosa, Paula; ,
Highlights: Globally, distribution of seasonal influenza vaccine doses is trending upwards. Inequities persist in distribution of seasonal influenza vaccine across WHO regions. The rollout of Covid-19 vaccines may further impede influenza vaccination uptake. Countries may use the Covid-19 pandemic to improve existing immunization systems. Support to countries is critical for optimizing the benefits of influenza vaccines. Abstract: Sustainable demand for seasonal influenza vaccines is a component of national security strategies for pandemic preparedness. However, the ongoing COVID-19 pandemic has revealed many weaknesses in the capacity of countries to design and execute sustainable vaccination programs. An influenza pandemic remains a global threat and yet there is no global monitoring system for assessing progress towards influenza vaccination coverage targets. The International Federation of Pharmaceutical Manufacturers and Associations' (IFPMA) Influenza Vaccine Supply International Task Force (IVS) developed a survey method in 2008 to estimate seasonal influenza vaccination coverage rates, which in turn serves as a crude estimate of pandemic preparedness. It provides evidence to guide expanded efforts for pandemic preparedness, specifically for increasing COVID-19 vaccine immunization levels. Furthermore, the results presented herein serve as a proxy for assessing the state of pandemic preparedness at a global and regional level. This paper adds data from 2018 and 2019 to the previous analyses. The current data show an upward or stable global trend in seasonal influenza vaccine dose distributed per 1, 000 population with a 7% increase between 2017 and 2018 and 6% increase between 2018 and 2019. However, considerable regional inequities in access to vaccine persist. Three regions, Africa, the Middle-east, and Southeast Asia together account for 50% of the global population but only 6% of distributed seasonal influenza vaccine doses. This is an important finding in the context of the ongoing COVID-19 pandemic, as distribution of influenza vaccine doses in many ways reflects access to COVID-19 vaccines. Moreover, improving seasonal vaccine uptake rates is critical for optimizing the annual benefits by reducing the huge annual influenza-associated societal burdens and by providing protection to vulnerable individuals against serious complications from seasonal influenza infections.